2022
DOI: 10.1590/0100-3984.2021.0055
|View full text |Cite
|
Sign up to set email alerts
|

Radiological patterns of pulmonary fungal infection in pediatric hematology and oncology patients

Abstract: Objective: To describe the radiological findings in pediatric patients with hematological or oncological diseases who also have an invasive fungal infection (IFI). Materials and Methods: This was a retrospective study of all patients with IFI admitted to a pediatric hematology and oncology hospital in Brazil between 2008 and 2014. Clinical and demographic data were collected. Chest computed tomography (CT) scans of the patients were reviewed by two independent radiologists. Results: We evaluated the chest CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…CT Imaging in Paediatric IPA: Typical Findings Several studies have documented the CT imaging findings of children with IPA ( 123 [3,9,10,[23][24][25], predominantly in children with malignancy or undergoing HSCT. Most studies included a small number of patients, with one exception which described the CT and or plain radiograph findings in 110 children with IPA [3].…”
Section: Diagnostic Imaging In Ipamentioning
confidence: 99%
See 4 more Smart Citations
“…CT Imaging in Paediatric IPA: Typical Findings Several studies have documented the CT imaging findings of children with IPA ( 123 [3,9,10,[23][24][25], predominantly in children with malignancy or undergoing HSCT. Most studies included a small number of patients, with one exception which described the CT and or plain radiograph findings in 110 children with IPA [3].…”
Section: Diagnostic Imaging In Ipamentioning
confidence: 99%
“…A recent systematic review reported high specificity of the halo sign (> 90%) for diagnosis of invasive fungal disease (IFD) in immunocompromised adults and children [ 31 ] although data on specificity for IPA are conflicting [ 14 , 27 ]. Notably, although earlier paediatric studies report a lower frequency of the halo sign (0–11%) [ 3 , 10 , 23 ], prevalence is higher in more recent studies (56–100%), possibly reflecting improvements in CT resolution and earlier timing of diagnostic scans [ 9 , 25 ]. In two previous paediatric studies, presence of the halo sign was highly specific for pulmonary IFD, although very few patients with IPA were included [ 24 , 29 ].…”
Section: Diagnostic Imaging In Ipamentioning
confidence: 99%
See 3 more Smart Citations